Development and validation of an instrument for essential information for anaesthetic records - Maja, Raphael Ntlhane (My University, 2016)
Introduction Content validity is a rigorous scientific process that aims to address whether the items on a developed instrument are content valid or not. Content validation is therefore an important process in the development of virtually all instruments. The aim of this study was to develop an Anaesthetic Record Essential Information Instrument (AR Instrument) that contains the items that South African anaesthetic experts considers are the minimum essential items that should be included in all anaesthetic records. This expert validated contextual AR Instrument has a dual purpose: firstly it can be used as a standard against which existing AR records can be evaluated, secondly, it can be used to develop new anaesthetic records. Methods and results A prospective, exploratory and instrumental study design using Lynn's two-stage model of determination and quantification of content validity was followed in this study. The Development Stage, that initially involved a review of the literature by the researcher and followed by a peer group discussion with local experts where every item was debated until consensus was reached, resulted in an instrument with 44 items. This instrument was sent to national experts for validation in the Judgement-Quantification Stage. A four point Likert scale ranging from unimportant to essential information was used to grade each item. Only items deemed important or essential by the experts were retained. This resulted in 41of the 44 items being considered content valid. This entire instrument was quantified using the content validity index (CVI). Lynn suggests that for an instrument to be considered content valid, it should have a CVI of 0.8. The CVI of this AR Instrument is 0.9. This instrument is therefore content valid. Conclusion An AR Instrument has been drawn up using a rigorous scientific process to ensure content validity.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2016